Urgensi Penguasaan Ilmu Takhrij Hadis Untuk Meningkatkan Kemampuan Mahasiswa dalam Pembelajaran Hadis di STAIN Teungku Dirundeng Meulaboh - Marisa, Siti Nurkhafifah (LPPPI Publishing, 2024)
Hadith is a course that is studied in almost all study programs at State Islamic Universities. In addition, hadith is also the basis for legal issues discussed in courses related to law such as Fiqh, fiqh muamalah, siyasah, jinayah, mawaris and others. However, researcher saw that during the process of learning hadith in the tsudy program other than the Science of the Qur'an and Tafsir, it was found that many students were still not able to recite the hadith which was used as a postulate for a law when used in a discussion, even most of them did not know the term takhrij hadith. This paper aims to explain how important it is to learn and understand the science of takhrij hadith for all students at Islamic Universities because they will interact with hadiths related to the law that need to be ascertained the status of the hadith. The method used in this study is a qualitative method starting with observations and interviews with students in the Qur'an and Tafsir Study Program, Islamic Economic Law Study Program, Sharia Banking Study Program, Constitutional Law, Islamic Criminal Law and also the Islamic Religious Education Study Program STAIN Teungku Dirundeng Meulaboh. The results of the study show that the majority of students still do not know the science of takhrij hadith and do not understand how to check the authenticity of a hadiths or not unless it is stated in the reference they use. The researcher sees the importance of students knowing the science of takhrij hadith, at least knowing how to make a practical and easy takhrij, namely with a contemporary method (digital), either using software such as maktabah shamilah or directly online to trusted websites such as www.dorar.net or www.islamweb.net. At least students have the knowledge to extract hadith from its original source (ma??dir al-a?liyah) so that the status of a hadith used as a postulate for a law in their learning is known. In addition, they can take advantage of this knowledge of takhrij to check the validity of a hadith that is now widely spread among the public or on social media quickly and easily.